RanGTP targets p97 to ranBP2, a filamentous protein localized at the cytoplasmic periphery of the nuclear pore complex - Delphin, Christian; Guan, Tinglu; Melchior, Frauke; Gerace, Larry (Molecular biology of the cell, 1997)
RanBP2, a protein containing FG repeat motifs and four binding sites for the guanosine triphosphatase Ran, is localized at the cytoplasmic periphery of the nuclear pore complex (NPC) and is believed to play a critical role in nuclear protein import. We purified RanBP2 from rat liver nuclear envelopes and examined its structural and biochemical properties. Electron microscopy showed that RanBP2 forms a flexible filamentous molecule with a length of ∼36 nm, suggesting that it comprises a major portion of the cytoplasmic fibrils implicated in initial binding of import substrates to the NPC. Using in vitro assays, we characterized the ability of RanBP2 to bind p97, a cytosolic factor implicated in the association of the nuclear localization signal receptor with the NPC. We found that RanGTP promotes the binding of p97 to RanBP2, whereas it inhibits the binding of p97 to other FG repeat nucleoporins. These data suggest that RanGTP acts to specifically target p97 to RanBP2, where p97 may support the binding of an nuclear localization signal receptor/substrate complex to RanBP2 in an early step of nuclear import.
Gesehen am 06.09.2023